Implementasi kepemimpinan digital pada keterampilan abad 21 life and career skills di SMK - Anisa, Dewvy Nur; Hidayati, Dian (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The habitual use of digital technology in schools, especially in SMKs that are directly connected to the digital industrial world, is one of the tasks of the school principal to prepare and ensure that the human resources they have are in accordance with the needs of their educational institutions. Digital life and career skills habituation is very important in the implementation of SMK education to prepare students for a connected and digitized future and increase work effectiveness in schools. The importance of habituation of digital life and career skills still gets a poor response to the application of habituation. This study aims to describe the strategies carried out by the principal as a leader on 21st Century Life and Career Skills at SMK Muhammadiyah 1 Yogyakarta. this research uses descriptive qualitative methods with data triangulation. The implementation of Digital Leadership on 21st Century Life and Career Skills at SMK Muhammadiyah 1 Yogyakarta has been proven to improve school quality and graduate quality. This is evidenced by the increase in digital skills of graduates who get a positive response from the industrial world. The industry's interest in the human resources produced has an impact on close collaboration with schools, as evidenced by the number of industries that partner and involve school human resources in industrial projects. This success is achieved through joint collaboration between the principal, teachers, staff, students and parents. The principal's digital leadership plays an important role in designing digital habituation in every school program. Awareness of the need for digitalization is the basis for continuous renewal of the school management system and teaching and learning activities. Digital habits throughout the school community, including the use of digital systems and innovations in the school's digital systems, are tangible evidence of successful digital transformation at SMK Muhammadiyah 1 Yogyakarta.